PENINGKATAN HASIL BELAJAR IPA MELALUI PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF DI KELAS V - Ningsih Ningsih (Perspektif Ilmu Pendidikan, 2012)
The low effectiveness of teachers in teaching makes students feel less enthusiasm in learning and their learning outcomes become low. The purpose of this research is to overcome the problem by utilizing interactive learning CD in a classroom action research. Taking place at SD Negeri 09 Pagi, Pademangan Barat, Jakarta Utara, this research was conducted in the fifth grade with 40 students on the topic of Human Digestive Organs, as from October through December 2011. The selection of interactive learning CD was based on the students’ preference to learn using audiovisual media. Data were collected by using the monitoring instrument sheet activities of teacher and students, test instrument, field notes, and recording of the learning in the form of photographs. After three cycles, the research findings indicated gradual improvement of the students’ learning achievement and passed the mastery learning level. The research implication is the science students’ learning outcomes will improve using Interactive Learning Media CD as it can motivate the students learn actively.